Editorial - Kostis C. Koutsopoulos (European Journal of Geography)
Yorgos Photis was my spiritual son, my student, my advisee, my helper, my colleague, my friend, my confidant and regrettable the sack of box to relieve my anxieties and worries. He suddenly left this world to meet his maker, who I am certain will show His mercy on such a fine man. Once I read a father's eulogy for his son, which fits exactly how I feel about Yorgos The sunflowers, the lilies and the lush green grass looked cheery, so long as you were around. Do you think they will ever look green again, once the meaning in life I have lost is found? Yorgos I wished I had remembered that passage more often and mainly practiced it when you were around me! But I remember the first time I called you in my office, as a young professor who care about his students, trying to deciphered the unkind remarks of a fellow professor about you. I am so proud that you have proved him so wrong. We worked together and you finished your undergraduate thesis, your PhD, and you climbed all the academic grades. You followed my steps in a more successful manner and became a professor of Geographical Analysis and Locational Planning, a department head, associated editor of the European Journal of Geography, president of the Hellenic Geographical society, and member of the board of EUROGEO- the European Association of Geography. I want to declare that I will continue to show my feelings for you, so that I will talk about you because I am proud of you. I will talk about you, because you deserve to be remembered. I will talk about you, because even though you not physically with me, you are never from my mind. I will talk about you, because you are part of me, a part that I could never ignore or disown. I will talk about you because I love you still and always will. Nothing will ever change that. The passing of Yorgos Photis has been a great loss to his family, the university, the department and the lab he was serving, as well as the Hellenic Geographical society, the European Journal of Geography and EUROGEO he was committed to their advancements. My sincere condolences Kostis Koutsopoulos Editor in chief EJG